Low temperature investigation on dielectric properties of carbon doped copper oxide. Issue 1 (30th April 2021) - Bitra, Hema Chandra Rao; Rao, A. Venkateswara; Babu, K. Suresh; Rao, G. Narsinga
Abstract: Carbon-doped copper oxide (CuO)1 -x C x ( x  = 0, 0.05 and 0.1) samples were synthesized by solid state reaction method, and sintered at 850 °C for 12 h. An X-ray diffraction (XRD) result shows that the structure of the samples was monoclinic. Dielectric studies were carried for these samples in the temperature range 80 K − 300 K between the frequency range 20 Hz − 1 MHz via impedance analyzer. The permittivity and tangent loss values of the doped samples increase with increasing doping concentration. In AC conductivity study, the conductivity mechanism of the 0% and 10% carbon doped samples follows correlated barrier hopping (CBH) model and 5% carbon doped sample follows quantum mechanical tunnelling (QMT) model. The temperature-dependent conductivity curve seems to obey the Arrhenius behavior. The activation energy values have been calculated from the frequency-dependent conductivity curves. The cole–cole plot shows the formation of grain and grain boundary in the samples.